Working in the killing fields forensic science in Bosnia - Ball, Howard 1937- (Potomac Books, 2015)
While the specificities of individual wars vary, they share a ubiquitous aftermath: the task of finding and identifying the "disappeared." The Bosnian war of the early 1990s that destroyed the sovereign state of Yugoslavia is no exception